Designing Safety System for BK16 Based on Grafcet - Phan, Thi Huyen Chau (Old Journal, 2019)
The technology process in BK16 wellhead satellite platform is to separate the gas and the oil from gas-water mixture. Therefore, the construction in BK16 is very dangerous due to the flammable and explosive possibility. In order to ensure the safety for people and equipment, it is obligatory to set up the safety system with absolute reliability and satisfies SIL 3 – safety level for BK16. The main function of this system guarantees that crude oil and gas are not leak, and if there has a leak the system will be reacted by closing or opening a series of valves such as: blowdown valve, process shutdown valve, emergency shutdown valve and monitoring the signals from level and pressure sensors of production separate tank to minimize losses. To reduce design time and programming, Grafcet method is applied because of the characteristics of safety system is to control many of ON-OFF valves.